(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
Composite materials, formed by combining two or more distinct phases, have become indispensable in sectors such as aerospace, automotive, marine, and sports manufacturing due to their high strength-to-weight ratio and design flexibility. However, unlocking their full potential requires innovative processing methods that overcome the limitations of traditional techniques, such as long cycle times, high production costs, and geometric constraints. This paper reviews several advanced fabrication techniques that are transforming composite manufacturing. Additive manufacturing (AM), including Fused Deposition Modeling (FDM) and Direct Ink Writing (DIW), enables customized fiber orientations and complex geometries. Automated Fiber Placement (AFP) and Automated Tape Laying (ATL) enhance speed and precision, reducing human error. Resin Transfer Molding (RTM) and Vacuum-Assisted RTM (VARTM) improve fiber wetting and reduce voids in large-scale components. Out-of-Autoclave (OoA) methods offer cost-effective alternatives to traditional autoclave curing, while novel heating and consolidation approaches—such as microwave, induction, and ultrasonic curing—advance the speed and quality of production. Collectively, these innovations improve efficiency, mechanical performance, and sustainability, pointing to a new era of composite manufacturing.